"A Fantasy of Untouchable Fullness": Melancholia and Resistance to Educational Transformation. Issue 1 (February 2017) - Stillwaggon, James
Abstract: The progressive language of growth and development that informs our shared ideal of the educated subject also informs the curricular structure of schooling, in which new learning builds upon established knowledge and students' development depends upon their desire to take on those identities associated with various achievements of knowledge. Each re‐creation of the student's identity requires a new production of the student's former identity as an uneducated self — a negative statement of the self‐overcome, fashioned in the language of the curriculum. But what of those objects of attachment or aspects of the child's identity that can neither be integrated in the student's educated identity nor accounted for as a recognizable lost object of childhood? In this essay James Stillwaggon argues that considering the student subject in terms of its melancholic attachments offers some alternatives to thinking of student identity primarily in terms of its progressive learning function. Julia Kristeva's treatment of melancholia as "asymbolia, " or against the representational function of language, is especially significant to this discussion, as it highlights the melancholic's resistance to the most basic educational purpose, namely the further engagement of the subject in language.